2014
DOI: 10.1089/mdr.2013.0087
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Molecular Characterization of AmpC-Producing Clinical Isolates ofEscherichia colifrom Southeastern Iran

Abstract: AmpC hyperproducing E. coli isolates exhibit significant resistance to cephalosporins. This work showed that strains hyperproducing chromosomal AmpC could be as frequent as strains with plasmid-mediated AmpC hyperproduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 12 publications
0
5
1
Order By: Relevance
“…In Asia, the percentage of clinical E.coli isolates that is pAmpC positive varies over a wider range. The lowest prevalence has been reported in studies in Japan (0.12% and 1.7% of E.coli [46, 47]), Iran (2.8% of E.coli [48]) and China (2% of E.coli [49, 50]). In a study in Turkey, 10.9% of clinical E.coli isolates carried pAmpC genes [23].…”
Section: Discussionmentioning
confidence: 99%
“…In Asia, the percentage of clinical E.coli isolates that is pAmpC positive varies over a wider range. The lowest prevalence has been reported in studies in Japan (0.12% and 1.7% of E.coli [46, 47]), Iran (2.8% of E.coli [48]) and China (2% of E.coli [49, 50]). In a study in Turkey, 10.9% of clinical E.coli isolates carried pAmpC genes [23].…”
Section: Discussionmentioning
confidence: 99%
“…This study showed that prevalence of bla CMY-2 , bla CMY-42 , and bla DHA genes among AmpC β-lactamases producers were 39%, 1%, and 17.5%, respectively. In a study carried out by Shayan et al [23] in Iran, the prevalence of bla CMY gene among 392 isolates of E. coli was investigated. They reported that 13 (3.3%) isolates were identified as AmpC producers, which 11 of the 13 isolates contained the bla CMY gene.…”
Section: Discussionmentioning
confidence: 99%
“…[ 19 20 ] In another Iranian study, 3.3% of E. coli isolates produced AmpC β-lactamases. [ 13 ] A study from Canada showed that the annual incidence rates of AmpC were 1.7, 4.3, 11.2, and 15 per 100,000 residents for each year, respectively. [ 21 ] Jabeen et al .…”
Section: Discussionmentioning
confidence: 99%
“…This resistance mechanism has been found around the world, can cause nosocomial outbreaks, and appears to be increasing in prevalence. [ 13 ] This study was undertaken to characterize ESBL and AmpC producers among E. coli by PCR, which were initially screened by phenotypic method.…”
Section: Introductionmentioning
confidence: 99%